Understanding the language of silence: awareness on reporting child maltreatment cases among UiTM Sungai Buloh Dental Students / Siti Syafiqah Abdul Aziz ... [et al.] - Abdul Aziz, Siti Syafiqah; Rabun, Mohd Nazir; Ayob Khan, Nur Fathiha (Universiti Teknologi MARA Cawangan Kedah, 2020)
This study examines the correlation between the attitudes, knowledge, behaviours, and years of education factors on the level of awareness of reporting child maltreatment cases among dental students in UiTM Sungai Buloh. A cross-sectional survey among Dental students in UiTM Sungai Buloh was engaged and employed for this study. Among 196 of the questionnaires distributed and returned, only 140 were useable. The associations between attitudes, knowledge, behaviours & years of educations, and level of awareness of reporting child maltreatment among dental students were thoroughly examined and analysed. The findings of this study revealed that all factors namely knowledge, attitudes, behaviours, and years of education were associated with the level of awareness of reporting child maltreatment among dental students. The majority of the students in UiTM Sungai Buloh had a moderate level of awareness of reporting child maltreatment cases. The findings are limited to the context of the study. This study will also arouse the interest and awareness of the situation to report child maltreatment. While it is envisaged that Dental offices can facilitate community awareness on child abuse and neglect in several ways. Some suggestions were also highlighted in this study to improve the present situation.